Marketing organically produced food products in Greece: Challenges and opportunities - Zotos, Yorgos; Ziamou, P.; Tsakiridou, Efthimia (My University, 1999)
The purpose of this paper is to explore the demand and supply characteristics of organically produced food products in Greece. Two large-scale surveys were conducted. The purpose of the first survey was to investigate consumers' awareness and intention to purchase organic products, consumers' perceptions and attitudes toward organic products, and reasons that hinder the purchase of organic products. The second survey was directed at the managers of chain-store supermarkets and its purpose was to examine their attitudes toward organic versus conventional products, and the challenges they are facing in marketing organic products. The paper concludes with the managerial implications of our findings.
Keywords: Greece; Green consumers; Green marketing; Green products; Organic food; Retail